Demystifying Tourists’ Intention to Visit Destination on Travel Vlogs: Findings from PLS-SEM and fsQCA - Pantas H. Silaban; Wen-Kuo Chen; Bernard E Silaban; Andri Dayarana K. Silalahi; Ixora Javanisa Eunike; Hanna Meilani Damanik (Ital Publication, 2023)
With the advent of digital technologies (i.e., social media), tourism has evolved its marketing strategies. Even though published literature discusses the importance of tourism content on social media from various consumer perspectives, much more work must be done to examine how consumers make travel decisions based on tourism content. This study proposes a model for analyzing travel intent based on consumer motivations (e.g., novelty, entertainment, and relaxation) to watch social media travel videos. Consumers' travel intentions are influenced by trust and parasocial relationships. Through an online survey, 215 responses were collected and analyzed using a structural equation modeling (SEM) approach using Smart-PLS 3.0 and fuzzy set qualitative comparative analysis (fsQCA). In the study, relaxation ranked most highly among the three motivations for viewers to watch travel videos on YouTube for building parasocial relationships. In contrast, consumers seeking entertainment are more likely to form trust, which will result in consumers' intentions to travel. Based on intermediate solutions generated by the fsQCA, two causal configurations can be used to explain consumer travel decisions influenced by social media tourism content. The study also discusses theoretical and practical guidelines in depth. Doi: 10.28991/ESJ-2023-07-03-015 Full Text: PDF